Photokeratoscopy in fitting contact lens after penetrating keratoplasty. Issue 1 (January 1986) - Manabe, R.; Matsuda, M.; Suda, T.
Abstract : The formula based on keratometric readings which is generally used is unsatisfactory for fitting contact lenses after penetrating keratoplasty, possibly owing to lack of information on the peripheral corneal toricity. In these studies a photokeratoscope was used to examine the entire graft topography. In all cases the corneal configuration became more normal after suture removal, but a considerable toricity still remained, especially near the graft-host junction. One month after removal of sutures spherical hard contact lenses (polymethylmethacrylate, PMMA) were fitted to 30 patients in accordance with data obtained by computerised analysis of the photokeratograms. Of the 30 patients (contact lens wearers) 27 (90%) obtained a stable vision of better than 20/30 for eight hours daily, and 24 (80%) achieved a stable vision of 20/20 for their full waking hours. After one year the contact lens wearers showed a significant decrease in the extent of astigmatism when compared with the non-contact-lens wearers (10 patients). These results suggest that the photokeratoscope can be more useful than ordinary keratometers in fitting contact lenses after keratoplasty, and that hard contact lenses have moulding effects on the graft topography.